Horace Porter papers - Porter, Horace, 1837-1921.
Correspondence, diary, speeches, biographical material, family papers, photographs, and other papers relating to Porter's service during the Civil War, as secretary to President Ulysses S. Grant, and as U.S. ambassador to France. Documents his career with the Pullman Company and the New York, West Shore & Buffalo Railroad; activities with the Union League of America; interest in Republican Party politics; and role in the inauguration of William McKinley. Includes correspondence relating to Porter's search for the body of John Paul Jones; notes pertaining to his book, Campaigning with Grant (1897); and correspondence as president of the Grant Memorial Commission (1891-1897). Correspondents include A.N. Blakeman, George Edward Payson Dodge, James Henry Duncan, Marcus Alonzo Hanna, John Hay, David Rittenhouse Porter, Sophie K. McHarg Porter, Albert B. Pullman, George Mortimer Pullman, and Elihu Root.
U.S. Army officer, railroad official, and diplomat.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Blakeman, A. N. -- 1840- -- Correspondence; Dodge, George Edward Payson, -- 1839-1904 -- Correspondence; Duncan, James Henry, -- 1793-1869 -- Correspondence; Grant, Ulysses S. -- 1822-1885.; Hanna, Marcus Alonzo, -- 1837-1904 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Jones, John Paul, -- 1747-1792.; McKinley, William, -- 1843-1901 -- Inauguration; Porter, David Rittenhouse, -- 1788-1867 -- Correspondence; Porter, Sophie K. McHarg, -- -1903 -- Correspondence; Pullman, Albert B. -- Correspondence; Pullman, George Mortimer, -- 1831-1897 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Porter family; Grant Memorial Commission; New York, West Shore & Buffalo Railroad; Pullman Company; Republican Party (U.S. : 1854- ); Union League of America; Diplomatic and consular service, American -- France; Railroads -- New York (State); France -- Foreign relations -- United States; United States -- Foreign relations -- France; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1865-1900.; Army officers; Diplomats; Railroad officials